Social Media Use Behavior and Social Media Disorder Among Faculty of Public Health Students During the COVID-19 Pandemic - Amelia, Tiara; Zainita, Ulfi Hida; Martha, Evi (Kesmas, 2023)
Excessive use of social media can lead to vulnerability to social media disorder, which is significantly related to the trend of mental health problems among college students. This study aimed to assess the prevalence of social media disorder among college students and to determine the relationship between the number of social media accounts, the total duration of social media use, and social media disorder. This cross-sectional study collected data through an online survey of 201 college students from the class of 2021 in the Faculty of Public Health, Universitas Indonesia. This study used the Social Media Disorder scaleand univariate and bivariate analysis to analyze the data. The prevalence of social media disorder was 23.9%; 93% of students were classified as high-duration social media users, and 58.2% had more than 10 accounts. Statistically, there was a significant relationship between the number of accounts (p-value= 0.045) and social media disorder. However, there was no significant relationship between the duration of social media use and social media disorder (p-value = 0.560). As a suggestion, the self-regulation factor must be considered an independent variable in predicting social media disorder among college students.